Avifauna Diversity in Kangean Archipelago - Irham, Mohammad (Masyarakat Zoologi Indonesia, 2016)
Research on the avifauna of Kangean Archipelago were conducted between 2007-2008. Objective of the studies were to obtain new data on the species numbers and community diversity at the main islands in various types of habitat. Three methods were applied i.e. opportunistic observation, point counts and mist netting. Each method would be complemen-tary in order to get a complete list of Kangean avifauna, while point counts were intended to be used for community di-versity study. A total of 82 species were recorded from which some of them especially migrating birds were new to the island. The richest diversity was found in natural habitat i.e. natural forest (28 species, Shannon index = 3.07), open area (32 species, Shannon index = 3.18) and mangrove (34 species, Shannon index = 3.09). Avian diversity was poor at teak plantation with only 26 species observed (Shannon index = 2.86). The threats to avian communities were apparent at song birds such as white-rumped shama and hill mynah. Those birds were hardly encountered during the survey. To be con-cluded, Kangean archipelago were richer in avifauna diversity than previously known, however hunting pressure and illegal logging might become serious threats to its existence.